Da vontade imperfeita à instituição do estado civil em Kant - Ribeiro, Gabriel Reis Pires (2017)
The aim of this study is to examine the need for the institution of the Civil State within the philosophical thought of Immanuel Kant. In the first chapter a part of Kantian practical thought will be analyzed, which is a piece of all the rational thought proposed by the philosopher. In the second chapter will be analyzed the concept of law and the possibility of having the property of an object. Finally, in the third chapter an study will be made about the relation of external freedom and coercion in the scope of the Civil State. To carry out this endeavor, it is necessary to work with the concept of imperfect will, which befalls all human beings and which impedes us from infallibly following the dictates of pure practical reason. This consequence of this is that when we act with the intention of satisfying our own interests, that is, when we yield to our own desires and inclinations, we thereby preclude the external freedom of other individuals and the peaceful coexistence of this external freedom in life in society. This raises the following question: how is life in society possible, ensuring the external freedom of individuals and free coexistence among wills other than one’s own? Would there be some type of driving force capable of conducting my imperfect will, and thereby allowing free coexistence among different wills? The response proposed in accordance with analysis of the Kantian text is that such an assurance of external freedom will only be brought about through the advent of the Civil State or Public Law, since only this State has a driving force capable of offering such a guarantee, namely, coercion. If this thereby occurs, it is because, just as inclinations are particular to us, coercion also has an empirical nature and is able to effectively restrain these inclinations that make the external freedom of individuals impossible. Thus, for the purpose of granting coexistence in freedom among diverse wills, the transition from the State of Nature to the Civil State will be necessary.